Protozoal and bacterial infections, including the gut microbiota, in wild rodents and the effects of environmental and host variables on their composition - Goertz, Sarah (2020)
Chapter 1 will detail the gut microbiota composition of wild house mice (Mus musculus domesticus) on the Isle of May and specifically focus on the spatial variability of the gut microbiota.